Effects of filler content and various coupling agents on properties of polypropylene/cocoa pod husk biocomposites - Koay, Seong Chun (School of Materials Engineering, 2015)
In this research, the processing torque of PP/CPH biocomposites were obtained during the melt compounding using a Brabender® Plastrograph intermixer. Then, the rheological properties of PP/CPH biocomposites were also investigated by using data from processing torque. The tensile properties of PP/CPH biocomposites were studied, such as tensile strength, elongation at break and tensile modulus. The tensile fracture morphological properties of PP/CPH biocomposites were investigated by scanning electron microscopy (SEM). Meanwhile, the thermal properties of biocomposites were carried out using differential scanning calorimetry (DSC) and thermogravimetry analysis (TGA). Besides that, water absorption test was carried out to investigate kinetic of water absorption of PP/CPH biocomposites by using Fick's Law. The Fourier transform infrared spectroscopy (FTIR) was used to determine the functional group of unmodified and modified CPH or biocomposites.